2006
DOI: 10.1074/jbc.m604671200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MAPKs in B Cell Receptor-induced Down-regulation of Egr-1 in Immature B Lymphoma Cells

Abstract: The immediate-early gene egr-1 (also known as NGFI-A, krox24, zif268, and tis8) encodes a transcription factor containing three tandem zinc finger motifs that bind to GC-rich DNA elements in the promoters of a range of target genes to activate their transcription (1). egr-1 expression is elicited in response to a diverse variety of signals, including growth factors, cytokines, lipopolysaccharide, serum, irradiation, stress, hypoxia, and urea, in many cell types, including neuronal cells, epithelial cells, fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…by guest www.bloodjournal.org From involved in cell survival, growth, and differentiation [32][33][34] suggested to us that Egr1 may be important for the ability of LMP2A to accelerate tumor onset in the presence of deregulated MYC. That Egr1 induction is downstream of BCR signaling 24,33,38 and LMP2A can be described as a BCR signaling "mimic" leant further support to our hypothesis. However, Egr1 function, at least the amount that could be blocked by expression of a dominant negative Egr, 24 does not appear to be required for tumor acceleration by LMP2A ( Figure 5).…”
Section: Gene Expression Profiling In Mouse Models Of Bl 6855mentioning
confidence: 99%
See 2 more Smart Citations
“…by guest www.bloodjournal.org From involved in cell survival, growth, and differentiation [32][33][34] suggested to us that Egr1 may be important for the ability of LMP2A to accelerate tumor onset in the presence of deregulated MYC. That Egr1 induction is downstream of BCR signaling 24,33,38 and LMP2A can be described as a BCR signaling "mimic" leant further support to our hypothesis. However, Egr1 function, at least the amount that could be blocked by expression of a dominant negative Egr, 24 does not appear to be required for tumor acceleration by LMP2A ( Figure 5).…”
Section: Gene Expression Profiling In Mouse Models Of Bl 6855mentioning
confidence: 99%
“…32,[35][36][37] In B cells, Egr1 is induced by BCR signaling. 24,33,38 Given that LMP2A is a signaling molecule that is functionally similar to the BCR, 10,11,22 we hypothesized that induction of Egr1 in LMP2A/-MYC mice may contribute to their accelerated tumorigenesis. 20,21 To test the functional importance of Egr1 in our transgenic model, we used a transgenic mouse expressing a DN Egr in B cells.…”
Section: Egr1 In Lmp2a/-myc Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egr1 up-regulation in prostate cancer cells is thought to promote cell growth and transformation through increased expression of cyclin D1 (15,16). However, Egr1 expression is either down-regulated or promotes apoptosis in other cancer cell lines (17)(18)(19), indicating cell-type specific responses. Egr2 expression has been primarily reported to promote apoptosis through transactivation of p53, FasL, Bak, and BNIP3 or suppress proliferation through PTEN expression (20 -22).…”
mentioning
confidence: 99%
“…19 Of interest, EGR-1 function has been shown to be dependent on ERK1/2 phosphorylation. 20 APC is a serine protease with a well characterized anticoagulant activity. Recent studies have demonstrated that APC has antiinflammatory and cytoprotective activities, which are not attributed to the anticoagulant activity of APC.…”
mentioning
confidence: 99%